The travel writer's handbook how to write, and sell your own travel experiences - Zobel, Louise Purwin 1922- (Surrey Books, 2007)
"Comprehensive guide to writing, researching, publishing, and marketing articles, stories and books about travel. Includes travel tips and advice for the writer" - - Provided by the Publisher.